ORTHODONTIC-SURGICAL APPROACH TO A CLASS III MALOCCLUSIONASSOCIATED TO NEW TECHNOLOGIES: CASE REPORT - Gustavo Fernando Sines Teixeira; Vicente Telles; Alexandre Ramalho Salvaterra; Lara Carvalho Freitas Sigilião (Portal de Periódicos da Marinha do Brasil, 2019)
Class III maloclusions are challenging for clinical orthodontics due to its multifactorial etiology and the craniofacial growth's unpredictability. Numerous skeletal and dental profiles associated with Class III maloclusions can result from mandibular prognathism, maxillary retrusion or association of both. After growth is ceased, treatment of these conditions is limited to dental compensation or orthodontic-surgical treatment. This article reports the case of a patient with Class III skeletal and dental malocclusion, treated with orthodontics and bimaxillary orthognathic surgery. This treatment plan was chosen due to the impossibility of orthodontic camouflage and to improve aesthetics and function. Data were collected through a review of medical records, study models, radiographs, cone beam computed tomography, and intra and extraoral photos. The treatment achieved the desired functional and aesthetic results, with adequate intercuspidation between the dental arches, increased volume of the face's middle third region, and reduction of chin's projection.